Death due to sickle cell anemia: autopsy diagnosis - Dhawle, Manjusha Shripad; Tangde, Ashwini Radhakrishan; Rathod, Santosh Govind; Bindu, Rajan S. (International Journal of Research in Medical Sciences, 2017)
Background: Sickle cell disease (SCD) is well known and is the commonest hereditary hematological disorder which is associated with increased mortality and morbidity. They are group of inherited haemoglobinopathies caused by the occurrence of hemoglobin S (Hbs) in homozygous or heterozygous form or in combinations of Hbs with another hemoglobin such as Hbsc or beta thalassaemia (Hbs-thal). Sickle cell syndromes are remarkable for their clinical heterogenecity including their presentations as sudden and unexpected death due to sickle cell crises. While doing autopsy in cases of deaths with no apparent cause and physical over activity medical officer must keep in mind the possibility of death due to vasoocclusive crisis in sickle cell disease. Aim of the study was to create awareness among the physicians and relatives / public and to minimize future unexpected death from complications or crisis from SCD. Methods: This is a retrospective study of 10 cases carried in the department of pathology, in tertiary care hospital and covers a period from January 2009 to December 2016. These cases were brought dead to the casualty with a history of sudden death. After post mortem examination, the specimens were sent for histopathological examination. Results: The record of 10 cases was reviewed. Out of our ten cases 7 were male and 3 were females. The youngest person was 17-year female and oldest was 65 years male. In clinical history 3 cases had complains of chest pain (30%), 3 others had complained of breathlessness (30%), 2 had history of unconsciousness (20%), one case had complained of abdominal pain (10%) and one case had a history of fall and injury (10%). Microscopic examination of each organ was carried out. Organs like lungs, liver, spleen, kidneys, heart and brain showed wide spread congested vessels which were stuffed with RBC. Conclusions: We present this study to emphasize that sickle cell crisis is one of the cause of sudden unexplained death and highlight the importance of considering sickle cell disease as a cause of death in cases with no apparent cause.